Use of Electronic Mail In the Virginia Cooperative Extension Service - Thomas R. McAnge Jr.; Michael T. Lambur (Journal of Applied Communications, 1988)
The level of usage, appropriateness, and effectiveness of electronic mail within the Virginia Cooperative Extension Service was studied. More than 20,000 electronic mail records and the contents of 200 electronic mail messages were analyzed. We determined that, during the past 12 months, a minimum of 13,000 notes were routed electronically from campus staff to county and city Extension offices. The most frequent type of message sent was a request for information. We also learned that more than 95% of the field offices respond to electronic mail within three working days. We concluded from the study results that electronic mail is a fairly common communication method in Virginia and Extension staff generally are making appropriate use of electronic mail.